2006
DOI: 10.1001/archneur.63.9.1312
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Weight Loss May Precede Diagnosis in Alzheimer Disease

Abstract: To determine the association of weight loss and the onset of dementia of the Alzheimer type (DAT) and to characterize the rate of weight change over time in older adults (aged 65-95 years) who develop DAT vs those who remain without dementia.Design: Rates of weight change were investigated in older adult research participants (N = 449) who were enrolled as control subjects without dementia and followed up longitudinally (6 years on average) at the Alzheimer's Disease Research Center, Washington University Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
192
3
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(215 citation statements)
references
References 65 publications
(91 reference statements)
15
192
3
5
Order By: Relevance
“…Our result regarding weight loss being associated with increased dementia related mortality risk fits with studies using clinical dementia as end point (10)(11)(12)(13)(14)(15)(16)(17)(18). Most previous studies investigate weight change in old age, typically above 65 years or older, where reverse causality might be a plausible explanation for the association between weight loss and dementia.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our result regarding weight loss being associated with increased dementia related mortality risk fits with studies using clinical dementia as end point (10)(11)(12)(13)(14)(15)(16)(17)(18). Most previous studies investigate weight change in old age, typically above 65 years or older, where reverse causality might be a plausible explanation for the association between weight loss and dementia.…”
Section: Discussionsupporting
confidence: 86%
“…A better understanding of the association between body weight and dementia may be achieved by studying weight trajectories and patterns from midlife into old age (1). Studies with weight at multiple time points have generally reported weight loss (10)(11)(12)(13)(14)(15)(16)(17)(18) or weight instability (19) to be associated with increased dementia risk. However, many of these studies are limited to weight trajectories in old age, and might be prone to reverse causality because dementia and preclinical dementia might cause weight loss (1,20).…”
Section: Introductionmentioning
confidence: 99%
“…34,35 There are also somatic changes that precede the onset of dementia that may provide important clues, including accelerated weight loss, 36 gait disturbances, physical frailty, 37 and slowed psychomotor speed 36 (Table 1). Memory complaints are thus the most reliable and easiest to test for signs of early AD.…”
Section: Ad Diagnosis Algorithmmentioning
confidence: 99%
“…In a sample of clinically well-characterized older adults who were cognitively healthy at enrollment, an acceleration in the rate of weight loss was a harbinger of the change from nondemented status to AD [9]. Luchsinger et al also reported a relation between weight loss and a higher dementia risk in an elderly sample (hazard ratio: 1.8; 95% confidence interval: 1.2-2.9) [10].…”
mentioning
confidence: 98%